AICCRA Curriuculum Design Concept Note - Curtis, Ashley (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report summarizes the design specifications proposed for the curriculum platform, a key activity of the AICCRA project. The AICCRA curriculum platform will be a resource that enables institutions to establish and continually develop and implement curricula that support key competencies and skills in climate information services (CIS) and Climate Smart Agriculture (CSA) prioritized by stakeholders in regions. The AICCRA curriculum platform activity is being led by RUFORUM. However, as part of the AICCRA project, the climate services cluster, together with AICCRA CSA and regional program collaborators, is supporting some activities related to the platform, including platform design specifications. Initial engagement between the AICCRA team and RUFORUM in early-mid 2022 on the curriculum platform activity resulted in some key decisions related to the curriculum platform.